2020
DOI: 10.3847/1538-3881/ab91b2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Evolution of Stellar Rotation Using Galactic Kinematics

Abstract: The rotational evolution of cool dwarfs is poorly constrained after ∼1–2 Gyr due to a lack of precise ages and rotation periods for old main-sequence stars. In this work, we use velocity dispersion as an age proxy to reveal the temperature-dependent rotational evolution of low-mass Kepler dwarfs and demonstrate that kinematic ages could be a useful tool for calibrating gyrochronology in the future. We find that a linear gyrochronology model, calibrated to fit the period– … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 96 publications
1
40
0
Order By: Relevance
“…We also use kinematic ages of Kepler field stars to calibrate the model for old K and early M dwarfs, where there is a dearth of suitable open cluster calibration stars. These kinematic ages also reflect the stalled magnetic braking behavior seen in open clusters (Angus et al 2020).…”
Section: Stellar Agementioning
confidence: 56%
“…We also use kinematic ages of Kepler field stars to calibrate the model for old K and early M dwarfs, where there is a dearth of suitable open cluster calibration stars. These kinematic ages also reflect the stalled magnetic braking behavior seen in open clusters (Angus et al 2020).…”
Section: Stellar Agementioning
confidence: 56%
“…In order to learn about the magnetic activity of stars with photometric data, we can use rotational modulation that results from the presence of active regions on the stellar surface. Additionally, the study of stellar rotation can provide key information for the understanding of angular momentum transport (e.g., Aerts et al 2019;van Saders et al 2019;Angus et al 2020;Curtis et al 2020;See et al 2021). Several studies have been carried out on the basis of Kepler and K2 data to measure surface rotation periods in a large sample of stars (e.g.m McQuillan et al 2014;Santos et al 2019;Reinhold & Hekker 2020;Gordon et al 2021;Santos et al 2021); furthermore, combined with the precise ages of stars, such as those obtained with asteroseismology or for clusters, it is possible to improve the general understanding of rotation-age relationships (e.g., Barnes 2003;Mamajek & Hillenbrand 2008;Angus et al 2015;van Saders et al 2016;Hall et al 2021;Godoy-Rivera et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We also used kinematic ages of Kepler field stars to calibrate this model for old K and early M dwarfs, where there is a dearth of suitable open cluster calibration stars. These kinematic ages also reflect the stalled magnetic braking behaviour seen in open clusters (Angus et al 2020).…”
Section: Host Star Agementioning
confidence: 52%
“…When estimating the ages of K dwarfs using gyrochronology, it is essential to account for 'stalled magnetic braking'. Recent observations have revealed that rotational evolution is inhibited for middle-aged K dwarfs (Curtis et al 2019;Angus et al 2020). This stalled rotational evolution is thought to be caused by an internal redistribution of angular momentum (Spada & Lanzafame 2020).…”
Section: Host Star Agementioning
confidence: 99%